The usage of oil refining industry waste as vulcanization active ingredient of elastomeric composition - Kachkurkina, Iryna; Ovcharov, Valery; Schevchenko, Olena (Publishing House of Lviv Polytechnic National University, 2009)
The influence of composite component perlite DPh-Zn, that is the waste of oil refining industry, on the formation of properties complex of rubber mixes and their vulcanizates on the basis of apolar cis-1,4-polyisoprene and butadiene-nitrile rubbers of various polarity has been investigated. It has been established that perlite DPh-Zn is the effective vulcanization active component of multifunctional action capable at 10.0 mass frac. concentration to replace in full or in part traditional accelerators, vulcanization activators, stabilizers, and can be recommended for use in industrial elastomeric compositions for rubber goods manufacturing. Досліджено вплив композиційного інгредієнту – перліт ДФ-Zn, що являє собою відпад нафтопереробної промисловості, на формування комплексу властивостей гумових сумішей та їх вулканізатів на основі неполярного цис-1,4-поліізопренового та бутадієннітрильних каучуків різноїп олярності. Встановлено, що він є ефективним вулканізаційно-активним інгредієнтом поліфункціональної дії, здатним при концентрації 10,0 мас.час. цілком або частково замінити традиційні прискорювачі, активатори вулканізації, стабілізатори, і може бути рекомендований для використання в промислових еластомерних композиціях для виготовлення формових гумо-технічних виробів.
Використання відпаду нафтопереробної промисловості як вулканізаційно-активного інгредієнту еластомерних композицій
Keywords: oil refining waste; motor oils additive; perlite DPh-Zn; elastomeric composition; multifunctional action; cis-1,4-polyisoprene rubber; butadiene-nitrile rubber; accelerator; activator; stabilizer; відпад нафтопереробки; присадка до моторних олив; перліт ДФ-Zn; еластомерна композиція; інгредієнт поліфункціональної дії; цис-1,4-поліізопрен; бутадієннітрильний каучук; прискорювач; активатор; стабілізатор